The Politics Behind Omnibus Legislation: Flexibility and Power in Indonesia’s Lawmaking Process - Torik Abdul Aziz Wibowo (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2025)
The adoption of the omnibus method as a legislative strategy to address regulatory complexity in Indonesia has sparked considerable debate, given that it constitutes an entirely new approach within the country’s legal framework. This article seeks to examine two key dimensions. First, the political configuration underpinning the enactment of Law No. 11 of 2020 on Job Creation; and second, the subsequent incorporation of the omnibus method into Law No. 13 of 2022 on the Formation of Legislation, alongside the role of the Constitutional Court in adjudicating its constitutionality through judicial review. Methodologically, the analysis employs both historical and conceptual perspectives. The findings reveal, first, that an elitist political configuration significantly shaped the adoption of the omnibus method in the Job Creation Law. The asymmetrical composition of parliament, marked by the dominance of pro-government coalitions, enabled a highly flexible regulatory framework for its implementation. Second, the Constitutional Court, through its ruling, failed to provide clear constitutional guidance on the legitimacy of the omnibus method, thereby allowing the legislature and the president to amend the Job Creation Law via a Government Regulation in Lieu of Law (Perpu) a mechanism that effectively bypassed the constitutional mandate set forth in the Court’s own decision.